A cycloaddition approach to substituted anthraquinone systems as potential antitumor agents. - Pham, Thi Tham. (University of Ottawa (Canada), 1996)
In the cycloaddition approach towards the synthesis of the substituted anthraquinone derivative 8 as a potential antitumor agent, it was found that the tricyclic core of this target analogue could be generated by an intramolecular Diels-Alder reaction. The Diels-Alder precursor 34 was successfully synthesized starting from 3-methyl benzyl alcohol, metha-crolein and (2Z)-2-(ethenyl)-3-iodo-1- (p-methoxybenzyloxy)-2-propene; it readily underwent cycloaddition at approximately 40$\sp\circ$C to generate a cis-fused ring system 35. The stereochemistry of the cycloaddition product was unambiguously determined by X-ray structure of crystalline 41. Stereo-selective epoxidation of the ring C double bond with m-chloroperoxybenzoic acid was achieved for diol 48, where the functionality at C2 was a hydroxyl group. The synthesis of anthraquinone derivative 47b is also described.* ftn*Please refer to the dissertation for diagrams.
Keywords: Chemistry, Organic.